Mengatasi Perilaku Terlambat Masuk Sekolah Melalui Konseling Behavioristik Dengan Teknik Behavior Contract Pada Siswa SMAN 2 Bae Kudus - Nelly Marthalina; Indah Lestari; Sucipto (Conseils : Jurnal Bimbingan dan Konseling Islam, 2025)
The objectives of this study are 1) To find out what factors cause SMAN 2 Bae Kudus students to be late to school 2) To find out how the results of the application of behavioristic counseling with behavior contract techniques in overcoming behavior often late to school in SMAN 2 Bae Kudus students. The type of research used is a qualitative type of research with a case study approach. The subjects in this study are 2 students with the initials GR and NM from SMAN 2 Bae Kudus class XI F 11 which is a KKO class. The data collection techniques used are in the form of observation, interviews, documentation. To test the validity of the data using triangulation. The data analysis technique uses the data analysis of the miles and Huberman model. The results of this study show that there is a behavioral change in students from maladaptive behavior (late school attendance) to adaptive (coming to school on time) after the provision of behavioristic counseling services with behavior contract techniques. Thus, it can be concluded that the application of Behavioristic counseling with the behavior contract technique can overcome late school entry behavior in students of SMAN 2 Bae Kudus grade XI F 11.